Depression, Anxiety, and Quality of Life in a Cardiac Rehabilitation Program Without Dedicated Mental Health Resources Post-Myocardial Infarction - Carlos Bertolín-Boronat; Víctor Marcos-Garcés; Héctor Merenciano-González; María Luz Martínez Mas; Josefa Inés Climent Alberola; Nerea Perez; Laura López-Bueno; María Concepción Esteban Argente; María Valls Reig; Ana Arizón Benito; Alfonso Payá Rubio; César Ríos-Navarro; et al. (Journal of Cardiovascular Development and Disease)
Anxiety and depression are common after a myocardial infarction (MI), so psychological and psychiatric mental health (MH) interventions are recommended during Cardiac Rehabilitation Programs (CRP). We aim to evaluate anxiety and depression symptoms and quality of life in MI sufferers followed in a CRP without dedicated MH resources. We prospectively included 164 MI patients in our CRP without dedicated MH resources. Patient Health Questionnaire 2-item (PHQ-2) and Generalized Anxiety Disorder 2-item (GAD-2) questionnaires for depression and anxiety screening (altered if ≥3 points) and the 36-Item Short Form Survey Instrument (SF-36) to analyze four MH components and Mental Component Summary (MCS) were assessed at the beginning and after CRP. The mean age was 61.35 ± 10.76 years, and most patients were male (86.6%). A significant improvement in SF-36 mental components (from +5.94 ± 27.98 to +8.31 ± 25 points, p < 0.001) and SF-36-MCS (+1.85 ± 10.23 points, p = 0.02) was noted, as well as a reduction in depression and anxiety symptoms in PHQ-2 and GAD-2 (p < 0.001). However, 33 (20.1%) patients showed a positive screening for depression and/or anxiety at the end of the program. These patients were younger (56.6 ± 8.05 vs. 62.55 ± 11.05 years, p = 0.004) and showed significantly worse initial scores of SF-36 mental components, PHQ-2, and GAD-2 (p < 0.001). We conclude that a Phase 2 CRP without dedicated MH resources can achieve significant improvements in MH well-being after MI. However, one-fifth of the population had substantial depression and/or anxiety symptoms at the end of the program. This subset, characterized by worse initial MH scores, may benefit from specific MH interventions during CRP.